2020
DOI: 10.1093/jas/skaa278.409
|View full text |Cite
|
Sign up to set email alerts
|

PSV-22 The effects of flavoring agents on feeding behavior, feed efficiency, growth performance and temperament of newly arrived feedlot cattle

Abstract: Ninety steers (259.9 ± 36.18 kg BW) were used in a 56-d experiment to assess the effects of flavoring additives on feeding behavior, feed efficiency, growth performance, and temperament of newly arrived feedlot cattle. Steers were homogenously distributed by BW into six pens (15 head/pen) and pen was randomly assigned to one of 3 treatments (2 pens/treatment): a standard feedlot receiving diet (CT); or the same diet with a flavoring additive comprised of either sweeteners (SW) or a mix of basic tastes (MX) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In turn, turbid water significantly reduces immune response through many phases of inflammation and cell-mediated immunity processes (Mohammed, 2008;Chen et al, 2018). Vaccines should be re-suspended in freshwater resources with a pH near neutral, medium hardness, and no chlorine or other disinfectant residues (Alvarado, 2008;Ahmad, 2022). Poor water quality for dilution and delivery of live vaccines might negatively affect vaccine titers.…”
Section: Interaction Between Water Quality and Vaccine Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, turbid water significantly reduces immune response through many phases of inflammation and cell-mediated immunity processes (Mohammed, 2008;Chen et al, 2018). Vaccines should be re-suspended in freshwater resources with a pH near neutral, medium hardness, and no chlorine or other disinfectant residues (Alvarado, 2008;Ahmad, 2022). Poor water quality for dilution and delivery of live vaccines might negatively affect vaccine titers.…”
Section: Interaction Between Water Quality and Vaccine Efficiencymentioning
confidence: 99%
“…It was also shown that using Sudanese tap water to dilute the ND vaccination had no negative effects on the immune response. The optimum water for the dilution of vaccines also had low turbidity and TDS (Khalil and Khalafalla, 2011;Ahmad, 2022).…”
Section: Interaction Between Water Quality and Vaccine Efficiencymentioning
confidence: 99%